Groundwater impact on methane emissions from flooded paddy fields. (September 2015) - Rizzo, A.; Boano, F.; Revelli, R.; Ridolfi, L.
Highlights: Lower infiltration rates promote higher methane (CH4 ) emissions in paddy fields. Shallow aquifer reduces infiltration rates, increasing CH4 emissions. Drainage system can mitigate CH4 emissions from paddies under shallow aquifer. Abstract: High methane (CH4 ) fluxes emitted from paddy fields strongly contribute to the accumulation of greenhouse gases into the atmosphere, compromising the eco-compatibility of one of the most important world foods. A strong link exists between infiltration rates of irrigation water and CH4 emissions. Since depth to the groundwater table affects infiltration rates, a relevant groundwater impact is expected on CH4 emissions from paddy fields. In this work, a theoretical approach is adopted to investigate the aquifer effect on CH4 dynamics in paddies. Infiltration rates are strongly affected by the development of different connection states between aquifer and irrigation ponded water. A strong reduction in infiltration rates results from a water table near to the soil surface, when the system is hydraulically connected. When the groundwater level increases, the infiltration rate reduction due to the switch from disconnected to connected state promotes a relevant increase of CH4 emissions. This is due to a strong reduction of dissolved organic carbon (DOC) percolation, which leads to higher DOC availability for microbial CH4 production and, consequently, higher CH4 emissions. Our simulations show that CH4 fluxes can be reduced by up to 24% when groundwater level is decreased and the aquifer is disconnected from ponding water. In paddies with shallow aquifers, lowering the water table with a drainage system could thus represent a promising CH4 mitigation option.